THE IMPACT AMONG MENSTRUATION, MOTIVATION, AND INTELLECTUAL INTELLIGENCE ON THE ACHIEVEMENT OF FEMALE ATHLETES AT SMANOR TADULAKO SULAWESI TENGAH - Mydi L, Ana Ribka; Rahardjo, Hermawan Pamot; awang, fajar (Journal of Physical Education and Sports, 2024)
This research aims to analyze the impact of menstruation, motivation and intellectual intelligence on the performance of female athletes at SMANOR Tadulako, Sulawesi Tengah. This research is quantitative research using questionnaire, observation and interview data collection techniques. This research was carried out at SMA Negeri Olahraga Tadulako, Sulawesi Tengah. The sample in this study were 34 female athletes who were registered as athletes at SMANOR Tadulako and had participated in championships at both regional and international levels and received medals. The data analysis technique in this research uses a significance test with the help of the SPSS ver. 26. The research results show that the impact variables of menstruation, motivation and intellectual intelligence have a significant impact on the performance of female athletes at SMANOR Tadulako with an effectiveness contribution of 35%.  The conclusion of this research is that the variables impact of menstruation, motivation, and intellectual intelligence have an influence on the performance of female athletes at SMANOR Tadulako, Sulawesi Tengah.